Comparative Analysis of Good Cooperative Governance Implementation in Indonesian and Overseas Cooperatives: A Systematic Literature Review - Iyan Izazi Huwaina; Anisa Dwi Utami; Maryono; Lukman M. Baga (Journal of Creative Power and Ambition (JCPA), 2026)
Cooperatives in Indonesia still face a number of challenges that need to be addressed. One of these stems from the inadequate implementation of good cooperative governance. Applying good governance principles constitutes a vital foundation for enhancing cooperative performance and fostering public trust. Principles such as transparency, accountability, independence, responsibility, fairness, and equality serve as key aspects that strengthen cooperative management. This study aims to identify, analyze, and compare the implementation of Good Cooperative Governance (GCoG) principles among Indonesian cooperatives and successful overseas cooperatives, as well as to formulate recommendations for improving cooperative governance practices in Indonesia. The research employs a Systematic Literature Review covering Scopus, Google Scholar, Academia, and Neliti databases, supported by NVivo 12 software. The findings reveal that while both groups conceptually acknowledge these principles, international cooperatives apply them consistently and under proper oversight, resulting in superior performance. In contrast, implementation in Indonesia remains weak and often merely formalistic. It is concluded that governance success does not depend solely on regulations, but on the quality of execution. Therefore, comprehensive strengthening of principle implementation is required to enable cooperatives to develop optimally.